Pre-operative right ventricular echocardiographic parameters associated with short-term outcomes and long-term mortality after CABG. Issue 4 (December 2018) - Chowdhury, Mohammed Andaleeb; Cook, Jered M; Moukarbel, George V; Ashtiani, Sana; Schwann, Thomas A; Bonnell, Mark R; Cooper, Christopher J; Khouri, Samer J
Abstract : Background: This analysis aims to assess the prognostic value of pre-operative right ventricular echocardiographic parameters in predicting short-term adverse outcomes and long-term mortality after coronary artery bypass graft (CABG). Methods: Study design: Observational retrospective cohort. Pre-operative echocardiographic data, perioperative adverse outcomes (POAO) and long-term mortality were retrospectively analyzed in 491 patients who underwent isolated CABG at a single academic center between 2006 and 2014. Results: Average age of enrolled subjects was 66 ± 11.5 years with majority being male (69%). 227/491 patients had 30 days POAO (46%); most common being post-operative atrial fibrillation (27.3%) followed by prolonged ventilation duration (12.7%). On multivariate analysis, left atrial volume index ≥42 mL/m 2 (LAVI) (OR (95% CI): 1.98 (1.03–3.82), P  = 0.04), mitral E/A >2 (1.97 (1.02–3.78), P  = 0.04), right atrial size >18 cm 2 (1.86 (1.14–3.05), P  = 0.01), tricuspid annular plane systolic excursion (TAPSE) <16 mm (1.8 (1.03–3.17), P  = 0.04), right ventricular systolic pressure (RVSP) ≥36 mmHg (pulmonary hypertension) (1.6 (1.03–2.38), P  = 0.04) and right ventricle myocardial performance index (RVMPI) >0.55 (1.58 (1.01–2.46), P  = 0.04) were found to be associated with increased 30-day POAO. On 3.5-year follow-up, cumulative survival was decreased in patients with myocardial performance index (MPI) ≥0.55 (log rank: 4.5, P  = 0.034) and in patients with mitral valve E/e′ ≥14 (log rank: 4.9, P  = 0.026). Conclusion: Pre-operative right ventricle dysfunction (RVD) is associated with increased perioperative complications. Furthermore, pre-operative RVD and increased left atrial pressures are associated with long-term mortality post CABG.